L4-to-L4 nerve root transfer for hindlimb hemiplegia after hypertensive intracerebral hemorrhage - Teng-Da Qian (Wolters Kluwer Medknow Publications, 2022)
There is no effective treatment for hemiplegia after hypertensive intracerebral hemorrhage. Considering that the branches of L4 nerve roots in the lumbar plexus root control the movement of the lower extremity anterior and posterior muscles, we investigated a potential method of nerve repair using the L4 nerve roots. Rat models of hindlimb hemiplegia after a hypertensive intracerebral hemorrhage were established by injecting autogenous blood into the posterior limb of internal capsule. The L4 nerve root on the healthy side of model rats was transferred and then anastomosed with the L4 nerve root on the affected side to drive the extensor and flexor muscles of the hindlimbs. We investigated whether this method can restore the flexible movement of the hindlimbs of paralyzed rats after hypertensive intracerebral hemorrhage. In a beam-walking test and ladder rung walking task, model rats exhibited an initial high number of slips, but improved in accuracy on the paretic side over time. At 17 weeks after surgery, rats gained approximately 58.2% accuracy from baseline performance and performed ankle motions on the paretic side. At 9 weeks after surgery, a retrograde tracing test showed a large number of fluoro-gold-labeled motoneurons in the left anterior horn of the spinal cord that supports the L4-to-L4 nerve roots. In addition, histological and ultramicrostructural findings showed axon regeneration of motoneurons in the anterior horn of the spinal cord. Electromyography and paw print analysis showed that denervated hindlimb muscles regained reliable innervation and walking coordination improved. These findings suggest that the L4-to-L4 nerve root transfer method for the treatment of hindlimb hemiplegia after hypertensive intracerebral hemorrhage can improve the locomotion of hindlimb major joints, particularly of the distal ankle. Findings from study support that the L4-to-L4 nerve root transfer method can effectively repair the hindlimb hemiplegia after hypertensive intracerebral hemorrhage. All animal experiments were approved by the Animal Ethics Committee of the First Affiliated Hospital of Nanjing Medical University (No. IACUC-1906009) in June 2019.